CGIAR Food Systems Accelerator Kick-Off Workshop - Zulu-Hume, Mercy F.; Dahl, Hauke; Nkosi, Mahlatse; Ng'anga, Salome; Kirimi, Peter; Bohjanen, Carey; Njiru, AnnRita (2023)
This report provides an overview of the CGIAR Food Systems Accelerator (CFSA) program’s Kick-off workshop held at Norrsken House in Rwanda. The Kick-off workshop serves as a key milestone for the program because it is the official commencement of the technical assistance of the first cohort of 10 selected agribusinesses. It highlights the program’s objectives, addresses the challenges faced by agribusinesses in securing private sector investment, presents an outline of the needs for the APs as input for the program curriculum co-creation, and sets clear intentions for achieving WP 3’s objectives through the CFSA program.